2012
DOI: 10.1063/1.4766289
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the conduction band edge energy via hybridization in quantum dots

Abstract: Articles you may be interested inDetermination of heterojunction band offsets between CdS bulk and PbS quantum dots using photoelectron spectroscopy Appl. Phys. Lett. 105, 131604 (2014); 10.1063/1.4897301 Green synthesis of highly efficient CdSe quantum dots for quantum-dots-sensitized solar cells

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 22 publications
3
14
0
Order By: Relevance
“…The comparison between the experimental and theoretical onset energies are summarized in Table I. When compared to previously published data on a larger QD size 11 , we find that hybridization effects occur at much lower doping concentrations and fully support our hybridization model.…”
Section: Xas Analysis Of Energy Onsetsupporting
confidence: 49%
See 3 more Smart Citations
“…The comparison between the experimental and theoretical onset energies are summarized in Table I. When compared to previously published data on a larger QD size 11 , we find that hybridization effects occur at much lower doping concentrations and fully support our hybridization model.…”
Section: Xas Analysis Of Energy Onsetsupporting
confidence: 49%
“…2) for the QDs in this manuscript have yielded sizes of 24, 31, and 43Å. In prior work, however, we suggested that certain features present in XAS may be used to determine particle size 11 . Figure 3 displays Cd M 3 -edge XAS for a series of undoped CdSe QDs.…”
Section: A Use Of CD M3-edge Xas As Tracer For Quantum Dot Particle mentioning
confidence: 97%
See 2 more Smart Citations
“…The lowering of the HOMO level may be due to the energy level hybridization between Se and S anions at the interface of CdSe/CdS core/shell NCs. The hybridization phenomenon in NCs has been revealed with the XANES (X-ray absorption near edge structure spectroscopy) measurement [30]. The CV results with type II CdTe/CdSe NCs have indicated that the CV information comes from both the core and shell, and it is mainly from the shell in the case of thicker shell, so it is suggested that the E CV g value is affected by not only the electronic level of the CdSe core but also that of the CdS shell, and the electrochemical CV method reflects the information about shell in core/shell system if the surrounding shell is very thick, similar to the case of type II core/shell NCs [24].…”
Section: Resultsmentioning
confidence: 99%